Chiral and magnetic effects on the dispersion curves of an annular waveguide - Ganguly S.; Singh Kh.S.; Khastgir P.; Ojha S.P. (My University, 2025)
We present a theoretical study of electromagnetic wave propagation through an annular waveguide with a chiral material in its guiding region and a dielectric material in the cladding. The modal characteristic equation has been derived. As expected, chirality admittance and magnetic properties in the guiding region affect the modal behavior of the waveguide. It is found that if the permeability is held fixed, an increase in the chirality admittance in the guiding region results in a decrease in the number of guided modes. On the other hand, for a given chirality, an increase in permeability of the guiding region results in an increase in the number of guided modes. © 1997 John Wiley & Sons, Inc.